Kajian Literatur Pemanfaatan Teknologi Artificial Intelligence untuk Meningkatkan Keterampilan Abad 21 Siswa dalam Pembelajaran Kimia - Prastika, Nanda Diah; Anjarwati, Dewi; Awaliah, Meisya Adelia Salsabila; Hartandi, Dimas; Rahmadani, Agung; Erika, Farah (Jambura Journal of Educational Chemistry, 2024)
Current technological developments provide many changes, especially in the field of education. The development of technology requires humans to be able to adapt to life in this era. One of them is by utilizing artificial intelligence (AI) in chemistry learning to open the way to a new era in chemistry education. Literature review was carried out using the narrative literature review method to identify the role of AI in chemistry learning in improving 21st century skills. The application of AI in chemistry learning not only has a positive impact on 21st century skills, but also changes the way students interact with chemistry concepts and opens up new opportunities for students to understand chemistry concepts in more depth through enhanced learning media, interactive simulations, and predictions accurate. The application of AI has been widely applied in chemistry learning and has shown positive results in improving 21st century skills.